Tinjauan Yuridis Terhadap Praktek Kawin Tangkap Menurut Hukum Adat Yang Berlaku Di Sumba Barat Daya - Dorkas Inya Karere; Simplexius Asa; A. Resopijani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Arrest Marriage is a marriage process that is carried out by force, Capture Marriage is carried out by kidnapping the bride, kidnapped to become a wife. The captive marriages that are taking place now are not the custom of Southwest Sumba, especially the Kodi area. Based on the results of research in Limbu Kembe Village, (1) What is the philosophy of the practice of catch marriage according to customary law in force in Southwest Sumba? (2) What is the process for resolving the practice of catch marriage according to customary law in force in Southwest Sumba? The research method used in this research is normative research, namely research that is based on applicable legal regulations by examining various applicable laws and regulations related to the problem under study. Based on the results of the research and discussion, it can be concluded that the current practice of captive marriage is not the tradition/culture of Southwest Sumba, especially the Kodi area, but rather the practice of captive marriage which has developed by hiding behind cultural claims in order to avoid legal action.